Inhibition of neddylation causes meiotic arrest in mouse oocyte. Issue 11 (3rd June 2019) - Yang, Mo; Jin, Yimei; Fan, Siying; Liang, Xiaoling; Jia, Jialin; Tan, Zhongzhou; Huang, Tao; Li, Yuan; Ma, Teng; Li, Mo
ABSTRACT: Mammalian oocyte meiosis is a special form of cell division that provides haploid gametes for fertilization. Unlike in mitosis, post-translational modifications (PTMs) are more crucial during meiosis because of the absence of de novo mRNA transcription. As a classic PTM, protein neddylation is a biological process that mediates protein degradation by modifying cullin proteins and activating the Cullin-Ring E3 ligases. This process plays important roles in various biological processes such as autophagy and tumorigenesis. However, the function of neddylation in germ cells is unknown. In this study, we observed that the inhibition of neddylation by its specific inhibitor MLN4924 significantly arrests mouse oocyte at the stage of metaphase during meiosis. The arrested oocytes display impaired spindles with over-activation of spindle assembly checkpoint (SAC). Accordingly, we identified early mitosis inhibitor 1 (Emi1), a key inhibitor of anaphase-promoting complex/cyclosome (APC/C Fzr1 ), as a substrate of neddylation-mediated protein degradation. Thus, our study uncovered an unknown role of neddylation in female germ cells and suggests that proper neddylation is essential for oocyte maturation.